Control of the pH for marine microalgae polycultures: A key point for CO2 fixation improvement in intensive cultures. Issue 38 (May 2020) - Galès, Amandine; Triplet, Sébastien; Geoffroy, Thibault; Roques, Cécile; Carré, Claire; Le Floc'h, Emilie; Lanfranchi, Mélissa; Simier, Monique; Roque d'Orbcastel, Emmanuelle; Przybyla, Cyrille; Fouilland, Eric
Highlights: The highest conversion of CO2 into carbon biomass was reached at pH 7. The theoretical maximal biological conversion of CO2 was estimated to be ca. 60 %. Lower and higher pH favoured respectively the amoebae and copepod development. pH can be a tool for favouring one microalgal species among a natural assemblage. Abstract: Recently, CO2 recycling for the production of valuable microalgae has acquired substantial interest. Most studies investigating CO2 conversion efficiency in algal cultures were based on single species, although a stabilising effect of algal diversity on biomass production was recently highlighted. However, addition of CO2 into polyalgal cultures requires a careful control of pH; performance of CO2 conversion, growth and carbon biomass production are affected by pH differently, depending on the species of microalgae. This study investigates the efficiency of CO2 conversion by natural marine algal assemblage cultivated in open, land-based raceways (4.5 m 3, 10 m 2 ), working as high rate algal ponds (HRAP). Ponds were enriched with nitrogen and phosphate, pure CO2 was added and algal cultures were grown under three different fixed pH levels: pH 6, 7 and 8. The highest conversion of photosynthetically fixed CO2 into carbon biomass (40 %) was reached at pH 7, an intermediate level, due to the partial CO2 asphyxiation of algal predators (copepods, ciliates), while being under the suboptimal conditions for the development of marine amoebae. Under this pH, the theoretical maximal biological conversion of available CO2 into carbon biomass was estimated to be 60 % in naturally inoculated open ponds.